2021
DOI: 10.1007/s10529-021-03147-5
|View full text |Cite
|
Sign up to set email alerts
|

High-cell-density fed-batch cultivations of Vibrio natriegens

Abstract: Objectives With generation times of less than 10 min under optimal conditions, the halophilic Vibrio natriegens is the fastest growing non-pathogenic bacterium isolated so far. The availability of the full genome and genetic engineering tools and its ability to utilize a wide range of carbon sources make V. natriegens an attractive host for biotechnological production processes. However, high-cell-density cultivations, which are desired at industrial-scale have not been described so far. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…The second cultivation in optimized VN medium showed the same trend as the first one, but especially for the higher glucose concentration (20 g l −1 ), more acetate, pyruvate and lactate were produced and a lower pH value was reached, compared to the first cultivation. Previous studies also reported the production of organic acids, especially under anaerobic conditions ( Hoffart et al, 2017 ; Long et al, 2017 ; Payne et al, 1961 ; Thiele et al, 2021 ).…”
Section: Resultsmentioning
confidence: 97%
“…The second cultivation in optimized VN medium showed the same trend as the first one, but especially for the higher glucose concentration (20 g l −1 ), more acetate, pyruvate and lactate were produced and a lower pH value was reached, compared to the first cultivation. Previous studies also reported the production of organic acids, especially under anaerobic conditions ( Hoffart et al, 2017 ; Long et al, 2017 ; Payne et al, 1961 ; Thiele et al, 2021 ).…”
Section: Resultsmentioning
confidence: 97%
“…Cultivation temperature is an important factor that affects the cell growth and production of desired chemical. When the temperature decreased from 37 ℃ to 30 ℃ during fed-batch fermentation, the biomass of V. natriegens increased by 62%, while the concentrations of byproducts such as acetate and lactate significantly decreased [ 41 ]. Therefore, PYR15 and PYR32 were selected to determine the optimum cultivation temperature in fed-batch fermentation.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, setting up a slow, steady feed of substrate could help overcome substrate toxicity, substrate solubility, and/or enzyme inhibition. The influence many of these process parameters have on V. natriegens growth have recently been evaluated and can serve as a blueprint moving forward for optimizing melanin production ( Thiele et al, 2021 ). Further, cost savings can be gained by using an alternative promoter system, such as the copA promoter, or genomic integration of Tyr1 into the chromosome of V. natriegens , which would preclude the use of costly IPTG and antibiotics, respectively.…”
Section: Discussionmentioning
confidence: 99%